COUPLING MAINTAINABILITY INCREASE OF TRANSPORT VEHICLES POWER PLANTS BY APPLICATION OF ROPE ELASTIC ELEMENTS - Protsenko, V. O.; Klementyeva, O. Yu. (Science and Transport Progress, 2017)
Purpose. The paper should consider lowering the labour input of maintenance of drive gears operation of vehicles power plants at the expense of working out the coupling construction having low duration of substitution of elastic element and a justification of its force, power and strength parameters. Methodology. During development of coupling construction with increased maintainability the criterion of minimum average labour input of its reconstruction has been used. Constructive-power parametres of coupling were defined with the use of classical methods and statics and calculus theorems. Simulation of couplings operation is executed by numerical methods for couplings of concrete executions with the use of modern program complexes. Findings. Authors developed the coupling with rope elastic elements having low labour input of elastic element substitution due to multiple-purpose construction of tightening elements and pins with open slots in which the rope sequentially can be included is developed. The dependences are received, allowing to define power loads of elements of a coupling, and also to execute selection of ropes and calculation of strength of tightening elements. With obtained dependence the coupling with rope elastic elements for substitution of coupling Vulkan propulsion plant of the bulk ship of the project 2-95А/R is calculated and designed. The integrated definition of time for rope substitution in the offered coupling with application of specifications has displayed that for execution of this process it is necessary to expend about 150 minutes of time that is much less than 530 mines necessary for substitution of elastic membranes of base coupling Vulkan. Originality. The estimation of the basic constructive, power and strenght parametres of coupling with face installation of a rope with increased maintainability is executed. Practical value. Construction of a coupling with increased maintainability equipped with rope elastic elements is offered in the paper. Application of such coupling in power installations can reduce expenditures of time and resources to maintenance operation and to lower cost of transportations.